A Hands-On Approach to Statistical Mechanics Lectures: Estimation of the Boltzmann Factor Through the Viscosity Experiment of a Falling Ball - Ngia Masta; Amanda Violeta; Sederhana Laia (Program Studi Pendidikan Fisika, Universitas PGRI Semarang, 2026)
Statistical mechanics is the study of physics that relates macroscopic and microscopic parameters, often studied only with a theoretical approach, so it is relatively difficult to understand. For this reason, simple practical activities are needed to be connected with statistical mechanics, one of which is a viscosity experiment to determine the Boltzmann factor. This research was conducted to evaluate the viscosity value, coefficient of determination (R2), Reynolds number, activation energy and Boltzmann factor obtained from the experiment of dropping marbles in a tube containing cooking oil at a temperature variation of 303K-333K. Viscosity is calculated based on the observed terminal velocity of the ball using Stokes' Law. The magnitude of the activation energy is analyzed using the Arrhenius equation and the probability of fluid particles flowing was calculated using the Boltzmann factor. The results showed that the viscosity of cooking oil decreased with increasing temperature, with viscosity values ranging from 44-79 cP. The Reynolds number is evaluated in the range <2300 confirming laminar flow and suitable for Stokes' law. The activation energy of viscous flow was obtained as 11.489 kJ/mol with a coefficient of determination R² = 0.87712 which indicates a strong correlation between temperature and viscosity. The estimated number of moving particles based on the Boltzmann factor is evaluated to be 1.05% - 1.58%. This research validates that the hands-on approach can explain that the increase in kinetic energy of molecules at high temperatures reduces the viscosity of the fluid, thereby increasing the probability of fluid particles flowing.